Toward Understanding the Origin of the B[e] phenomenon in FSCMa Type Objects - Miroshnichenko, A. S.
Large amounts of circumstellar material accompany lives of most stars at different evolutionary stages. Formation mechanisms of these, often disk-like envelopes are not always clear. The B[e] phenomenon includes the presence of permitted and forbidden line emission and strong infrared (IR) excess in radiation observed from stars of the B and early-A types. It is found in several groups of mostly binary systems. The recently defined FS CMa group is thought to have their gas-and-dust disks due to an earlier strong mass-transfer between the binary system components. FS CMa objects seem to possess longliving disks, whose properties have not been studied well. I will be reviewing the group properties and results of a long-term monitoring program of some of its members with a focus on detected variations of the brightness and spectrum.
Keywords: Stars; Astronomy